1988
DOI: 10.1111/j.1440-169x.1988.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis Initiated by Cell Fusion in Dictyostelium discoideum

Abstract: D. discoideurn has two alternative developmental pathways. If cells of two complement matingtype strains, NC4 and HM1, fuse sexually, a giant cell is produced which subsequently develops into a macrocyst, the sexual structure of this organism. However, if fusion fails to occur and cells are starved, a fruiting-body is produced instead of a macrocyst. In this paper, a two-dimensional polypeptide gel electrophoresis study showed that giant cells produce specific polypeptides which may possibly be involved in mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…autoinhibitor, CFIF) to regulate other events of macrocyst formation. In an effort to identify proteins involved in ZGC differentiation, protein synthesis was assessed in zygotes produced both by mixed‐mating cultures and the synchronous (delayed‐mixed‐mating) development system (Moriyama & Yanagisawa, 1987; Saga & Yanagisawa, 1982). [ 35 S]‐methionine pulse‐labelled protein profiles were then resolved by two‐dimensional gel electrophoresis.…”
Section: Heterothallic Sexual Development Of Dictyostelium Discoimentioning
confidence: 99%
“…autoinhibitor, CFIF) to regulate other events of macrocyst formation. In an effort to identify proteins involved in ZGC differentiation, protein synthesis was assessed in zygotes produced both by mixed‐mating cultures and the synchronous (delayed‐mixed‐mating) development system (Moriyama & Yanagisawa, 1987; Saga & Yanagisawa, 1982). [ 35 S]‐methionine pulse‐labelled protein profiles were then resolved by two‐dimensional gel electrophoresis.…”
Section: Heterothallic Sexual Development Of Dictyostelium Discoimentioning
confidence: 99%
“…In the unicellular organism, Chlamydomonas reinhardtii, expression of a zygote specific gene is reported but its product is used to attack chloroplast DNA of one parent (Armbrust et al 1993 ATAATAATAATAATAATAATAATAATAATAATAATAACAATAATAATAGTAATAATAATAATAATAATAATAACAGT~T~T~T~TA 720 141N N N N N N N N N N N N N N N N S N N N N N N N N S N N N N AT~T~TTAACAAT~T~T~T~T~T~T~T~A~T~T~T~T~A~T~T~TTTTASI0 171 N N N I N N N N N N N N N N N N N N N I N N 95 accumulation of mRNAs, cellular maturation to the sexually competent state may include transcription of genes necessary for the post-fusion development. In our previous studies, notable alterations of the protein profiles after cell fusion were observed (Moriyama and Yanagisawa 1987). Detection of fewer alterations in the mRNA profiles revealed in this study may suggest that the translational control of gene expression governs early sexual development in D.…”
mentioning
confidence: 55%